The Effect of Employee Silence on Turnover Intention, with Burnout As a Mediation Variable and Coworker Support As a Moderating Variable - Herlin E. N. Lerebulan; Lia Amalia (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research was conducted to investigate the effect of Employee Silence to Turnover Intention by exploring the role of mediation Burnout which is moderated by Coworker Support which is designed using a survey design with a survey tool that uses a questionnaire and is distributed online. Respondents in this study were selected using the method convenience sampling with the criteria of generation Z employees who work in the mining industry in Indonesia, which are then analyzed using a structural equation technique, namely SEM PLS. The research results reveal that employee silence cause burnout resulting in increased withdrawal behavior and intention turnover intention of generation Z who work in the site office and head office; burnout mediate this direct relationship. In addition, as well as with coworker support can support the relationship between employee silence and turnover intention. This study can help managers to realize that employee silence have an influence on turnover intention from generation Z, and also helps managers identify the psychological consequences of employee silence.